(untitled) (International Journal of Agriculture and Sustainable Development, 2024)
This study presents an analysis of agricultural inputs and cropped area dynamics in Pakistan from 2012 to 2022, aiming to understand the relationships between key agricultural parameters. The analysis considers factors such as total cropped area, fertilizer offtake, import of fertilizers, and import of insecticides, utilizing data collected from reliable sources including the National Fertilizer Development Centre and the Pakistan Bureau of Statistics. Descriptive statistics, correlation analysis, and the coefficient of determination were employed to explore these relationships and their implications for agricultural productivity and sustainability. The findings reveal notable fluctuations in total cropped area, fertilizer offtake, and imports of fertilizers and insecticides over the study period. While correlations between cropped area and fertilizer offtake, as well as the import of insecticides, were modest, a negative correlation was observed between cropped area and fertilizer imports. These findings suggest nuanced interactions influenced by various factors beyond fertilizer usage alone, such as soil fertility, climate conditions, and economic considerations. The study underscores the importance of promoting balanced and sustainable agricultural practices, including judicious fertilizer use and integrated pest management strategies, to enhance crop yields, soil fertility, and environmental sustainability. Furthermore, it highlights the need for policymakers, researchers, and agricultural stakeholders to adopt holistic approaches that integrate various parameters to devise effective strategies for enhancing agricultural productivity, sustainability, and resilience in Pakistan. In conclusion, this analysis provides valuable insights into agricultural dynamics in Pakistan and offers recommendations for future research directions and interventions to address systemic challenges and ensure food security and environmental stewardship in the face of a changing world.